Digital Contract Disputes in the FinTech Era: Legal Analysis of Consumer Protection and the Obligations of the Parties - Rusdi Sanmas; Markus Suryoutomo; Arliyanda Arliyanda; Johannes Triestanto; Iwan Rasiwan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The rapid development of the Financial Technology (FinTech) industry has significantly transformed the delivery of financial services, including the execution of contracts in electronic form. Digital contracts offer greater efficiency, transparency, and accessibility for the public. However, these practices also present complex legal challenges, particularly regarding consumer protection and the obligations of the parties involved. Many digital contracts still rely on standardized, one-sided clauses that may disadvantage consumers, while FinTech providers often limit their legal liability. Existing regulations, such as Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law) and Law No. 8 of 1999 on Consumer Protection (UUPK), provide a normative legal framework to ensure the validity of digital contracts and safeguard consumer rights. Nevertheless, implementation in practice faces obstacles, including issues with verifying electronic signatures, clarity of contractual clauses, and the effectiveness of dispute resolution mechanisms. This study employs a normative juridical approach to analyze disputes in FinTech digital contracts in Indonesia, emphasizing the need for balance between the rights and obligations of all parties. The findings suggest a necessity for regulatory harmonization, improved legal and digital literacy among consumers, and the development of adaptive dispute resolution mechanisms, including faster and more efficient online dispute resolution alternatives. These efforts are expected to enhance legal certainty, foster consumer trust, and reduce the risk of disputes in the continually evolving FinTech landscape.